Qualitative exploration of the early experiences of opioid use disorder patients from private clinics after Russia’s invasion of Ukraine in five major cities in Ukraine - Mazhnaya, Alyona; Meteliuk, Anna; Pykalo, Iryna; Altice, Frederick L. (Frontiers in Public Health, 2023)
Introduction Following the full-scale invasion of Ukraine by the Russian Federation on 24 February 2022, over 6,000 patients were at risk of potential disruptions in treatment with medications for opioid use disorder (MOUD) in Ukraine. Before 2022, privatized MOUD clinics had emerged, partly driven by restrictive governmental policies and practices in state-funded facilities. Nevertheless, scant information exists regarding their operation and the patient’s experiences, especially during crises. This study seeks to elucidate the initial lived experiences of patients utilizing private MOUD clinics, integrating these insights with an analysis of the responding health system during war. Methods The findings are derived from 20 qualitative semi-structured interviews conducted between March and June 2022, engaging participants from five major Ukrainian cities: Kharkiv, Kyiv, Odesa, Poltava, and Zaporizhzhya. Employing a rapid analysis procedure, we examined the data through descriptive and analytical summaries aligned with the domains of the data collection instrument. Results Emergent themes encompassed stress and uncertainty following the invasion’s onset, challenges accessing MOUD, and consequent perceptions concerning state-funded versus private clinics. The study identified disruptions in the operation of private MOUD clinics across most cities examined. Issues pertaining to MOUD medication availability were linked to dosage reductions at state-funded clinics or pharmacy medication shortages or closures. Despite varied experiences at different MOUD clinics and cities, most participants continued their treatment. Discussion This qualitative exploration provides a perspective on lived experiences with MOUD treatment at private clinics amidst the initial months of the invasion, illuminating how the early days’ stress, access challenges, varied responses from private MOUD clinics, and precarious conditions informed or altered preferences regarding MOUD treatment options. Moreover, these findings corroborate previously documented efforts by myriad stakeholders to mitigate war-related disruptions to MOUD delivery. These insights contribute to the international understanding of health system navigation and resilience during major crises, offering valuable lessons for preparedness development.